# How do you solve # 6(-3v + 1) = 5(-2v - 2) #?

##### 1 Answer

Oct 28, 2017

v = 2

#### Explanation:

So, the first thing we need to do is expand the brackets:

6(-3v + 1) = (6 * -3v) + (6 * 1) = **-18v + 6**

5(-2v - 2) = (5 * -2v) + (5 * -2) = **-10v - 10**

Therefore:

-18v + 6 = -10v - 10

We can then simplify the equations by adding the values to each side (remember that when you add something to one side, you must do the same thing on the other side):

-18v + 6 (- 6) = -10v - 10 (- 6)

-18v = -10v - 16

Then, we can do the same thing with v:

-18v (+ 10v) = -10v - 16 (+ 10v)

-8v = -16

Then, divide both sides by -8 to get the value of v:

**v = 2**